Improving student’s science process skills through environment-based guided inquiry on biodiversity in outdoor learning - Shopiah Dhuha Siregar; S. Saefudin; R. Riandi (University of Muhammadiyah Malang, 2025)
The integration of guided inquiry, outdoor learning, and diverse school environments is essential for enhancing students’ Science Process Skills (SPS), particularly in biodiversity topics. This study aims to improve students’ SPS through the implementation of Environment-Based Guided Inquiry in Outdoor Learning on biodiversity. The research was conducted at MAS Darul Ulum Sipaho using a one-group pretest-posttest design involving 19 students from class X MIA. The learning intervention was conducted in various school environments, including gardens and plantations, enabling students to interact directly with natural phenomena. The instrument used was a science process skills test consisting of 19 multiple-choice items and 2 essay questions, which had been validated by experts and tested for reliability and validity. The Wilcoxon signed-rank test and N-Gain analysis were performed to assess improvement. Results showed a significant improvement in students’ SPS, with the mean pretest score of 43.79 rising to 90.11 in the posttest, and an N-Gain of 0.82 (high). The Wilcoxon test revealed a statistically significant difference (Z = -3.826, p < 0.001). Science process skills improved in all students, with 79% showing high gains and 21% moderate gains. All indicators increased; classification showed the highest gain (97%), while hypothesis formulation was the lowest (67%).